Groups combinatorics & geometry : Durham 2001 - Ivanov, A. A.; Liebeck, M. W. (Martin W.), 1954-; Saxl, J. (Jan), 1948- (World Scientific, 2003)
Over the past 20 years, the theory of groups, in particular simple groups, finite and algebraic, has influenced a number of diverse areas of mathematics. Such areas include topics where groups have been traditionally applied, such as algebraic combinatorics, finite geometries, Galois theory and permutation groups, as well as several more recent developments. Among the latter are probabilistic and computational group theory, the theory of algebraic groups over number fields, and model theory, in each of which there has been a major recent impetus provided by simple group theory. In addition, there is still great interest in local analysis in finite groups, with substantial new input from methods of geometry and amalgams, and particular emphasis on the revision project for the classification of finite simple groups. This important book contains 20 survey articles covering many of the above developments. It should prove invaluable for those working in the theory of groups and its applications.